Next Generation Spin Torque Memories - Kaushik, Brajesh Kumar; Verma, Shivam; Kulkarni, Anant Aravind; Prajapati, Sanjay; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book offers detailed insights into spin transfer torque (STT) based devices, circuits and memories. Starting with the basic concepts and device physics, it then addresses advanced STT applications and discusses the outlook for this cutting-edge technology. It also describes the architectures, performance parameters, fabrication, and the prospects of STT based devices. Further, moving from the device to the system perspective it presents a non-volatile computing architecture composed of STT based magneto-resistive and all-spin logic devices and demonstrates that efficient STT based magneto-resistive and all-spin logic devices can turn the dream of instant on/off non-volatile computing into reality.
Introduction to Magnetic Memories and Spin Transfer Torque -- Magnetic Tunnel Junctions (MTJs) -- STT MRAMs -- Hybrid MTJ-CMOS Digital Circuits -- Non-volatile Computing With STT MRAMs -- Spin Transfer Torque Based All Spin Logic (ASL) -- Non-volatile Computing With All Spin Information Processing -- References.
Keywords: Microtechnology; Microelectromechanical systems; Electronics; Electronic circuits; Microsystems and MEMS; Electronics and Microelectronics, Instrumentation; Electronic Circuits and Systems